Better Together: The Uses of Ecological and Socio-Economic Indicators With End-to-End Models in Marine Ecosystem Based Management - Tam, Jamie C.; Fay, Gavin; Link, Jason S. (Frontiers in Marine Science, 2019)
Ecological and socio-economic indicators are used as proxies for attributes of ecosystems and human communities, respectively. End-to-end models are used to predict how ecosystems will respond to alternative management actions and changing environmental conditions. Despite the importance of these two tools for Ecosystem-Based Management (EBM), there has been limited integration of ecological indicators directly into end-to-end models; the former are typically calculated post hoc with output from the latter. Here we explore how ecological indicators can be better incorporated into end-to-end models and examine the importance of this union with regards to cumulative impacts and indirect effects, setting management objectives, practical indicator selection, and applications to management. We conclude that the inclusion of ecological indicators in end-to-end models is not only feasible, but provides needed guidance on describing ecosystem status relative to strategic as well as tactical ecosystem-level management goals, and will escalate the implementation of EBM.